1993
DOI: 10.1159/000216887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Antiphospholipid Antibodies to Noncardiolipin Antigens in Systemic Lupus erythematosus

Abstract: The specificity and immunoglobulin isotype distribution of antiphospholipid (aPL) antibodies have been evaluated in 68 patients with systemic lupus erythematosus (SLE) by ELISA which employed a panel of 7 different PL antigens. A total of 49 patients (72%) were positive for aPL antibodies of different isotypes and directed to one or more PL epitopes. Prevalence of IgG anticardiolipin (aCL, 37%) was similar to that of the other negatively charged PLs phosphatidylserine (PS, 35%), phosphatidylinositol (PI, 35%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…It is interesting to note that no clustered reactivity to anionic or zwitterionic phospholipids was observed. In groups 1 and 2, where only one reactivity had been identified initially, the frequency of autoantibodies to other phospholipids is similar to that reported by Toschi et al (13). However, the lesser incidence of antibodies directed toward zwitterionic phospholipids reported by these investigators and others (4,14) was not seen in our series.…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note that no clustered reactivity to anionic or zwitterionic phospholipids was observed. In groups 1 and 2, where only one reactivity had been identified initially, the frequency of autoantibodies to other phospholipids is similar to that reported by Toschi et al (13). However, the lesser incidence of antibodies directed toward zwitterionic phospholipids reported by these investigators and others (4,14) was not seen in our series.…”
Section: Discussionsupporting
confidence: 91%
“…As suggested by Clancy et al (21), the antigens on apoptotic cells bound by autoantibodies may themselves be involved in the normal engulfment of apoptotic cells. SLE IgG might block molecules on the apoptotic cells that are necessary for recognition and facilitation of their uptake by macrophages, such as phosphatidylserine (PS) or C1q (22)(23)(24)(25). Otherwise, we showed in our study that preincubation with a peptide that blocks the IgG Fc region or blockade of Fc␥ receptors on the macrophage abrogated the inhibitory effect of the SLE autoantibodies.…”
Section: Discussionmentioning
confidence: 58%
“…Most data agree that the frequency of antibodies to anionic PLs is comparable to that of aCL [46,[48][49][50], which is due to the extensive cross-reactivity of aCL with other negatively charged PLs. Besides, patients with clinical features of the APS who have negative results for LA and aCL have occasionally been found having antibodies to other anionic PLs [51][52][53]. We have previously showed that aPI could be the main marker of APS and in some patients aPI was the only aPL detected [51].…”
Section: Critical Evaluation Of Elisas For Apl Other Than Aclmentioning
confidence: 99%